Cin: from pathological aspects to the efficiency of the methods usedin screening and follow up - Fonseca, Fernanda Villar; Tomasich, Flávio Daniel S.; Jung, Juliana Elizabeth (Brazilian Journal of Sexually Transmitted Diseases, 2012)
The cervix cancer is the second most common type of cancer in females. It is responsible for the death of until 250,000 women every year and about 80% of the cases occur in developing countries. This type of cancer still remains as one of the biggest problems in public health in developing countries, especially in Latin America and the Caribbean. Despite of this disease can be preventable, the cooperative efforts to implement screening programs, haven’t still reduced successfully the deaths from this disease. When pre-cancerous modifications are found in the cervical tissue and had an adequate treatment, can contribute to avoid the premature death of a great number of women. Frequently the discussion is about which test can be used according to the reality of developing countries. In this context, the efforts to the developing of new methodologies of screening, mainly in countries with few financial resources, is very important. It is endless and intense the present searching for tumor markers capable of, specifically, to attribute differentiated risks to tumors associated to HPV.